MANAJEMEN KANTIN SEHAT DALAM MENINGKATKAN KEGIATAN BELAJAR MENGAJAR (Studi Kasus di SMAN 3 Rangkasbitung) - Imas Tatu Sri Mulyani; Nana Suryapermana (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
The purpose of this study is (1). Describe healthy canteen service management planning (2) Describe the management of healthy canteen services (3) Describe the implementation of healthy canteen service management (4) Describe supporting factors for managing healthy canteen services (5) Describe the inhibiting factors for healthy canteen service management, and (6) in improving teaching and learning activities at SMAN 3 Rangkasbitung. This research uses a qualitative approach with descriptive analysis method, namely research to describe the management of healthy canteens in SMAN 3 Rangkasbitung objectively through data that actually exists and occurs. The data source consists of primary data and secondary data. In data collection tools are used in the form of documentation, observation, and interviews. The data analysis technique is carried out by following the steps which include; reduction and by selecting and sorting out data, important data is taken and unnecessary data is discarded. Based on the results of the study found that the principles of healthy canteen management of SMAN 3 Rangkasbitung are planned (health, educative, affordable prices and cooperation) that will help improve student learning activities, healthy canteens of SMAN 3 Rangkasbitung by running several socialization programs on canteens about healthy eating that have increased knowledge students, Supporters of SMAN 3 Rangkasbitung canteens already have healthy canteen standards. This has been proven by obtaining the Adiwiyata certificate from the Ministry of Food Security.